(untitled) (Bangladesh Journal of Pharmacology, 2013)
We aimed to investigate the pharmacoeconomic efficacy of ivabradine and nebivolol in treatment of stable angina pectoris patients with left ventricular dysfunction prospectively. Pharmacoeconomic analysis was performed by using cost minimization analysis, and cost effectiveness analysis. After 6 months treatment LVEF for the nebivolol group (17 patients, 50%) improved by (38 ± 6.5) to (41 ± 3.2), (p>0.05) and for the ivabradine group (17 patients, 50%) (37 ± 5.4) to (41 ± 2.3), (p>0.05), mean MET value in the nebivolol group increased from (3.7 ± 1.2) to (5.5 ± 1.6), (p>0.05), versus from (3.6 ± 1.5) to (5.5 ± 1.4), (p>0.05) in the ivabradine group, cost minimization analysis results showed a difference in the total cost of treatment was US 5288.7 in favor of nebivolol. The findings suggest that nebivolol is more cost-effective than ivabradine in the treatment of patients with left ventricular dysfunction.